The Impact of Training Given to Nulliparous Pregnant Women for Attaining Identity and being Satisfied with the Maternal Role - Soghra Jamshidbeiki; Zohreh Khakbazan; Mehrnaz Geranmayeh; Siyamak Tahmasebi; Abbas Mehran (Guilan University of Medical Sciences, 2017)
Abstract Introduction: Maternal role is competence, skill and satisfaction of a woman who, as a mother, has maternal understanding and feeling for the infant. Objective: This study aimed at determining the impact of training on nulliparous Pregnant women in attaining identity and satisfaction with the maternal role. Materials and Methods: This is a quasi-experimental intervention study. This study was conducted on 100 pregnant women referred to health centres affiliated to Tehran University of Medical Sciences in 2013. The sample consisted of 45 subjects in the intervention group and 47 subjects in the control group. Inclusion criteria were gestational age of 36 weeks or more, age of 18 and above, living with a partner, no physical or mental illness, no record of alcoholism and drug abuse, having at least passed third grade in secondary school, Iranian citizenship and no history of participation in courses on baby care. Training classes were held 3 times for pregnant women in the intervention group. The first and third sessions included training, slide shows with lectures and questions and answers; but the second session included practical training on baby showers and film screenings. At the end of these sessions, a booklet containing baby care training material was provided to the mothers. The booklet contained training material including umbilical cord care, how to breastfeed and related problems like fissures and mastitis, among others. It also included how to use iron and multivitamins, vaccination of infants, care for infants, their shower, their clothes, mother and infant nutrition, prevention and healthcare of infant in case of urinary tract burns and care and necessary actions in case of fever, diarrhea or bloating, etc.. In this research, data gathering tools included questionnaire (personal information and maternal identity questionnaire in the third trimester of pregnancy, maternal identity questionnaire in postpartum and maternal satisfaction questionnaire). Descriptive statistical and analytical tests including Chi-square test, Fisher's exact test, Friedman test as well as T-paired and independent T-tests were used to analyse the data. Results: Comparison of individual properties and maternal identity level before the intervention in two groups showed no significant difference (P> 0.05). Statistical test showed no statistically significant difference between the intervention and control groups in terms of maternal identity, in pre-training levels, 6 and 12 weeks after delivery; but mean maternal satisfaction in weeks 6 (P<0.001) and 12 (P<0.001) after delivery had a statistically significant difference between the two groups. Conclusion: According to this study, it seems that improvement in maternal identity has not been possible by short-term training and needs broader intervention. According to the impact of training on maternal satisfaction, it recommended to offer infant care training programmes for promoting a sense of empowerment in mothers for better child care